Evaluation of Lake Sentani Water Quality Using Pollution Index, STORET, CCME-WQI, BC-WQI, and NSF-WQI Methods - Bambang Suhartawan; Daawia Daawia (International Journal of Hydrological and Environmental for Sustainability, 2026)
Lake Sentani is the largest lake in Papua and serves as an important source of raw water, fisheries, and livelihoods for communities in Jayapura. Increasing anthropogenic pressures from settlements, agriculture, aquaculture, and tourism have raised concerns regarding the deterioration of its water quality. This study compared the water quality status of Lake Sentani using five assessment methods: Pollution Index (IP), STORET, CCME-WQI, BC-WQI, and NSF-WQI. Water samples were collected from five stations representing littoral, limnetic, and human-activity-influenced zones. The analyzed parameters included physical (temperature, TDS, TSS, turbidity, and Secchi depth), chemical (pH, dissolved oxygen, BOD₅, COD, nitrate, phosphate, ammonia, and sulfate), and biological (total coliform) indicators. The results indicated IP values ranging from 3.95 to 6.43 (lightly to moderately polluted), STORET scores from –20 to –44 (moderately to heavily polluted), CCME-WQI values from 47.3 to 71.2 (marginal to fair), BC-WQI values from 44.7 to 68.5, and NSF-WQI values from 46.1 to 70.3. Station S3 (Sentani Town) consistently exhibited the poorest water quality, whereas Station S4 (Ayapo) showed the best condition. Elevated BOD₅, phosphate, ammonia, and total coliform were identified as the principal parameters contributing to water quality degradation. The five assessment methods produced generally similar spatial patterns across the sampling stations, with Pearson correlation coefficients ranging from 0.89 to 0.97, although these correlations should be interpreted cautiously given the limited number of monitoring stations. Among the evaluated approaches, CCME-WQI provided a balanced assessment by integrating the scope, frequency, and magnitude of water quality exceedances, making it a suitable framework for routine monitoring of tropical lake ecosystems under the conditions examined in this study.